RANCANG BANGUN AUGMENTED REALITY PADA MEDIA PROMOSI PERUMAHAN VILLA GREEN AULIA - Al Haris, Firdhaus Hari Saputro (Prodi Teknik Informatika Universitas Sahid Surakarta, 2020)
The house will not be separated from everyday human, because the house is a human need as a place to live. Therefore, prospective home buyers should consider the choice of home. In a housing exhibition, the agents used the media in the form of mockups and printed brochures of interestable prints possible to sell housing products. Through promotional media brochures and mockups is not uncommon for prospective buyers are still confused to imagine the image or shape of the house to be built because the promotion is still using 2-dimensional objects that have a limited viewpoint. Agents also choose brochures rather than mockups in their promotional media because in the cost of making a maket the price is too expensive and must make some type of type. And to perfect the mock and the brochures, then in this study aims to apply augmented reality technology to describe the housing sold in the form of 3dimensional objects. After augmented reality is used, the Agent can promote the house to replace the maket and brochure with the marker. A marker is a pattern created, in the form of an image the camera will recognize. Data collection methods in this study using observation, literature study and documentation while the method of system development using the Multimedia Development Life Cycle (MDLC) method. Making this application using various software that is 3ds Max for creating object 3D, Unity3D to create augmented reality, and Photoshop to create layout design, marker, and brochure. The test results android device shows the application has been compatible with all smartphones with a minimum of 1GB of RAM. The results of user testing on 20 respondents as a tester, where the response of 97% states well to very well so that the application made accordingly with the expected.